Distortion-driven spin switching in electron-doped metal porphyrins. Issue 26 (14th June 2022) - Cojocariu, Iulia; Carlotto, Silvia; Jugovac, Matteo; Floreano, Luca; Casarin, Maurizio; Feyer, Vitaliy; Schneider, Claus Michael
Abstract : Different conformers can be stabilized for flexible porphyrins upon electron doping. The metastable flat conformer relaxes to the energetically favored distorted form, inducing spin switching in the chelated nickel ion. Abstract : Electron injection into electrode-supported metal complexes allows for charge redistribution within the molecule to be controlled. Here we show, for the first time, how the structural flexibility in electron-doped porphyrins is critical in defining charge localization by following the evolution of the spin state and charge distribution in the thermodynamically favored structure as a function of dopant dose and relaxation time. Two flexible transition metal-containing molecules are used as model systems, nickel and cobalt tetraphenylporphyrin, studied by combining a wide range of spectroscopic techniques with detailed DFT calculations.